THU0270 Immunosuppressive Therapy in Combination with Steroids in the Treatment of Giant Cell Arteritis. (9th June 2015) - Carbonella, A.; Berardi, G.; Biscetti, F.; Bosello, S.L.; Parisi, F.; Zoli, A.; Gremese, E.; Ferraccioli, G.
Abstract : Background: High glucocorticoids doses represent the standard of care in Giant Cell Arteritis (GCA) 1 . Objectives: The aim of the study was to assess the disease course and the adverse events in GCA patients treated with corticosteroids alone or in association with immunosuppressive drugs. Methods: 47 consecutive patients with GCA, treated with conventional therapy (steroids) or with combined therapy (Methotrexate+steroids or Cyclophosphamide+steroids) were analyzed. Disease relapses (defined as recurrence of clinical symptoms and increasing of inflammation markers) and adverse events were evaluated for a mean follow-up of 30.8 months (range 12-131). Results: Twenty-four patients (51.1%) were conventionally treated with glucocorticoids only, 12 (25.5%) with MTX+steroids, 11 (23.4%) with CYC+steroids. Patients treated with steroids only ("steroid") showed more disease relapses than those treated with immunosuppressive drugs ("CYC-MTX") (41.7% in "steroids" vs 13% in "CYC-MTX", p=0.049). The steroid starting dose was less than 1 mg/kg/day prednisone equivalents in 21.7% of patients in the "MTX-CYC" group. The minimum steroid maintenance dose (5 mg/day of prednisone equivalents) was obtained in a mean time of 5.3±4.2 months in the "CYC-MTX" and in 10.4±6.6 months in the "steroids" (p=0.005). The adverse events recorded were two cases of pneumonia in "CYC" and one case of transaminasitis in "MTX". The number of glucocorticoids side-effects were 19 in the "steroids" and 3 in the "CYC-MTX" subgroup. Conclusions: Immunosuppressive drugs (CYC or MTX) combined with steroids, in GCA patients, could lower the risk of disease relapses and the steroid exposure and side effects, without increasing adverse events. References: Mukhtyar C et al. European Vasculitis Study Group. EULAR recommendations for the management of large vessel vasculitis. Ann Rheum Dis. 2009;68:318-23. Disclosure of Interest: None declared